2020
DOI: 10.1097/sla.0000000000004426
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Pediatric Perforated Appendicitis in the New York City Metropolitan Region at the Epicenter of the COVID-19 Outbreak

Abstract: Objective: The aim of the study was to determine whether perforated appendicitis rates in children were influenced by the Coronavirus disease 2019 (COVID-19) surge. Background: Disruption of care pathways during a public health crisis may prevent children from obtaining prompt assessment for surgical conditions. Progression of appendicitis to perforation is influenced by timeliness of presentation. In the context of state-mandated controls and public wariness of hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
72
3
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 34 publications
14
72
3
5
Order By: Relevance
“…The most likely reason for the findings by Anteby and colleagues is a delay in arrival at the emergency department [2] . This corresponds to studies reporting significant increase in perforated and gangrenous appendicitis due to delay in seeking care during the COVID-19 pandemic [ 3 , 4 ].…”
supporting
confidence: 68%
“…The most likely reason for the findings by Anteby and colleagues is a delay in arrival at the emergency department [2] . This corresponds to studies reporting significant increase in perforated and gangrenous appendicitis due to delay in seeking care during the COVID-19 pandemic [ 3 , 4 ].…”
supporting
confidence: 68%
“…It has been reported that due to the impact of the epidemic, patients have reduced their visits to hospitals for fear of increased risks of COVID-19 infection. [ 7 ] The number of visits to the department of emergencysurgery decreased, [ 16 ] as well as the number of patients in other disciplines, including the postponing of urinary surgical procedures, [ 17 ] decreased outpatient hemodialysis, [ 18 ] interruption of organ transplantation, [ 19 ] and so on. The incidence of acute appendicitis has also decreased, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Most patients can achieve good therapeutic effect by timely appendectomy, [ 6 ] but the public health crisis caused by COVID-19 is a barrier to timely surgical treatment. Such as, during the COVID-19 outbreak, many patients described a delay in seeking assessment for their symptoms due to fears of in-hospital COVID-19 infection; [ 7 ] some COVID-19 patients also shown gastrointestinal symptoms, [ 8 ] which might interfere with doctors' timely and accurate diagnosis; hospitals would adopt more stringent epidemic prevention measures, [ 9 ] which also increased the time of each link from admission to discharge.…”
Section: Introductionmentioning
confidence: 99%
“… [32] , [33] , [34] , [35] Several authors have described performing nonoperative management of appendicitis during the current pandemic. [ 36 , 37 ] Kvasnovsky et al reported over half of all appendicitis cases failed initial nonoperative management, which was defined as persistence of pain, fever, or emesis after 12 – 24 hours. [36] Of the 30 patients undergoing surgical intervention, over half were diagnosed with uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%